2015
DOI: 10.1016/j.molonc.2015.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Determination of cell uptake pathways for tumor inhibitor lysyl oxidase propeptide

Abstract: The lysyl oxidase propeptide (LOX-PP) is derived from pro-lysyl oxidase (Pro-LOX) by extracellular biosynthetic proteolysis. LOX-PP inhibits breast and prostate cancer xenograft tumor growth and has tumor suppressor activity. Although, several intracellular targets and molecular mechanisms of action of LOX-PP have been identified, LOX-PP uptake pathways have not been reported. Here we demonstrate that the major uptake pathway for recombinant LOX-PP (rLOX-PP) is PI3K-dependent macropinocytosis in PWR-1E, PC3, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 120 publications
(162 reference statements)
1
24
0
2
Order By: Relevance
“…On the contrary, PI3K-independent macropinocytosis is linked to Cdc42 activation resulting in filopodia formation. 44,45 In the present study, we found that expression of onco-Dbl markedly induced the formation of stress fiber and thereby increased the quantities of lamellipodia ( Figure 6). These enhanced actin polymerizations and lamellipodia formation occur alongside macropinocytosis promotion but with the inhibition of CME and CvME (Figure 1), indicating that the macropinocytosis of Tat/pDNA is most likely PI3K-dependent and controlled by the Rac1 activation-mediated actin cytoskeleton rearrangement mechanism.…”
Section: Discussionsupporting
confidence: 60%
“…On the contrary, PI3K-independent macropinocytosis is linked to Cdc42 activation resulting in filopodia formation. 44,45 In the present study, we found that expression of onco-Dbl markedly induced the formation of stress fiber and thereby increased the quantities of lamellipodia ( Figure 6). These enhanced actin polymerizations and lamellipodia formation occur alongside macropinocytosis promotion but with the inhibition of CME and CvME (Figure 1), indicating that the macropinocytosis of Tat/pDNA is most likely PI3K-dependent and controlled by the Rac1 activation-mediated actin cytoskeleton rearrangement mechanism.…”
Section: Discussionsupporting
confidence: 60%
“…Therefore, the pathways of LOX-PP cell uptake were investigated in a variety of cell lines to assess for possible avenues to enhance uptake and therefore potentially block cancer cell growth and metastatic potential. Data demonstrated that macropinocytosis is employed by most cell lines, while clathrin-dependent pathways serve as secondary uptake pathways in some cell lines (Ozdener et al 2016). Ongoing work is focusing on modifying the structure of LOX-PP to enhance its uptake by cancer cells and increase its effectiveness, and to establish which targets are the most important in mediating the tumor inhibitor properties of LOX-PP.…”
Section: Lox-pp and Tumor Suppressionmentioning
confidence: 99%
“…The major obstacle to easily capturing and analyzing the CTCs lies in their rarity, as CTCs are quite literally one in a million or billion among other cells in the blood[26]. Another challenge has to do with the heterogeneity of CTCs, as they can vary in surface protein expression, size, and physical characteristics, and often travel through the bloodstream in clusters[14].…”
Section: Liquid Biopsy Biomarkers and Biogenesismentioning
confidence: 99%